ANALYSIS OF VERBAL LEARNING ON LEARNING - Devi Sakinah Nasution; Neviyarni Neviyarni (Universitas Trunojoyo Madura, 2020)
This article, it discusses the analysis of verbal learning using references from relevant studies, verbal learning situation that a person needs in learning to clear, concise and concise languange. In verbal learning there are four analyzes in it, namely : (1) responce and association learning, (2) stimulus discrimination, (3) stimulus selection, (4) stimulus coding.